2009
DOI: 10.1111/j.1467-8276.2009.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Export Sectors and Rural Development

Abstract: The export base hypothesis is that a region’s growth is led by export demand, given perfectly elastic factor supplies. It is a rationale for “sector-based” rural development policies, and it is formalized by input-output models. But it is contested by modern trade, migration, and growth theories, and there is little research about its empirical relevance. We investigate the hypothesis for contemporary U.S. rural development by estimating the influence of export sector employment on subsequent rural development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 63 publications
5
65
1
1
Order By: Relevance
“…Finally, these models are static, thus neglecting changes in technology, innovation as well as the often lengthy adjustments to the economic injections provided by mining ventures. For this latter reason, they also tend to be of limited use when depicting scenarios for the future (Kilkenny and Partridge 2009).…”
Section: Methodological Approaches In Previous Empirical Researchmentioning
confidence: 99%
“…Finally, these models are static, thus neglecting changes in technology, innovation as well as the often lengthy adjustments to the economic injections provided by mining ventures. For this latter reason, they also tend to be of limited use when depicting scenarios for the future (Kilkenny and Partridge 2009).…”
Section: Methodological Approaches In Previous Empirical Researchmentioning
confidence: 99%
“…With most energy-boom counties being rural and somewhat remote, gaining agglomeration economies is an important element of future growth. 10 U.S. National Interregional Highway Committee's (1944) report shows maps of the proposed "military" highway system, which is remarkably similar to what was eventually constructed in the 1950s, 1960s, and 1970s. In general, the literature suggests that counties and states that are initially more intensive in mining tend to grow less over the long-term (Papyrakis and Gerlagh, 2007;Freeman, 2009;Kilkenny and Partridge 2009;Lobao, 2013;James and Aadland 2011). Many of the reasons for mining-intensive regions to lag in the long-run are discussed above.…”
Section: Boom-bust and The Natural Resource Cursementioning
confidence: 99%
“…Many of the reasons for mining-intensive regions to lag in the long-run are discussed above. Yet, another reason is simple labor-saving technological change in the goods sector means that declining numbers of workers are needed to extract the same resource (Kilkenny and Partridge, 2009). Much of the literature has focused on the institutional and governance problems for mining-intensive regions that lead to corruption and rent-seeking (Papyrakis and Gerlagh, 2007;Van der Ploeg, 2011), though Michaels (2010) suggests that U.S. local institutions are strong enough to avoid the resource curse.…”
Section: Boom-bust and The Natural Resource Cursementioning
confidence: 99%
“…In general, prior studies analyzing the relationship between an increase in exports and job creation have shown mixed results. Thus, a set of studies finds that economic development based on an increase of exports clearly leads to job creation (Bustos 2011;Ernst 2005;James and Fujita 2000;Kiyota 2014); another showed that the liberalization of trade among countries reduces the demand for labor (Greenaway et al 1999;Leichenko 2000;Kilkenny and Partridge 2009). In other words, there may exist a positive or negative impact on new employment, depending on the difference between the market expansion effect and the labor demand shrinkage effect.…”
Section: Smes' Basic Factors and Job Creationmentioning
confidence: 99%